Language Revitalisation in Gaelic Scotland: Linguistic Practice and Ideology - Tabasum Niroo, Woloyat (Journal of International Students, 2021)
Through their native languages, certain groups of people claim political, social, geographical, and ethnic identity and a legal base for their existence. Colonialism, however, has vanished minority spoken languages in many parts of the world. Additionally, despite claims of a “global village,” the advent of internationalization has further isolated indigenous languages in some parts of the world. Revitalizing and preventing those languages from dwindling from their spoken communities is crucial for scholars of linguistics, sociology, cultural studies, and education. Dunmore, in the book Language Revitalisation in Gaelic Scotland: Linguistic Practice and Ideology, offers profound perspectives on preventing the potential loss of Gaelic language in Scotland drawing from empirical research.